Building Academic-Religious Culture Based on Religious Moderation - Chotimah, Chusnul; Tanzeh, Ahmad; Siddiq, Syahril (IAIN Ponorogo, 2022)
Academic culture is a norm of thought, attitude, and behavior that becomes a reference for all university academics. Islamic Religious Colleges through Ma'had al-Jami'ah serve as gatekeepers of tafaquh fi al-din in the smiling Islam. It maintains the pillars of character building, moderation, tolerance, local wisdom, anti-violence, and commitment to the nation. It is not the exclusivism of Islam, even the extremist. Building an academic-religious culture based on religious moderation is essential to prevent extremism by strengthening religious practices based on the essence of religious teachings. Through this qualitative method, this paper explores data related to the pattern of religious-academic development based on religious moderation, forms of supporting activities for academic-religious culture, and the contribution of Ma'had al-Jami'ah in building an academic-religious culture based on religious moderation. This paper contributes to an academic-religious development model based on religious moderation in higher education. Budaya akademik merupakan norma pemikiran, sikap, dan perilaku yang menjadi acuan bagi seluruh sivitas akademika perguruan tinggi. Perguruan Tinggi Agama Islam melalui Ma'had al-Jami'ah berfungsi sebagai penjaga gerbang tafaquh fi al-din dalam konteks Islam yang ramah (the smilling Islam), mempertahankan pilar pembentukan karakter, moderat, menekankan aspek toleransi, kearifan lokal, anti-kekerasan, dan komitmen terhadap bangsa, bukan sebaliknya, Islam yang eksklusif bahkan cenderung ekstrim. Tulisan ini menggali data terkait pola pengembangan akademik keagamaan berbasis moderasi keagamaan, bentuk-bentuk kegiatan pendukung budaya akademik keagamaan, dan kontribusi Ma'had al-Jami'ah dalam membangun budaya akademik keagamaanberdasarkan moderasi agama. Tulisan ini menggunakan penelitian kualitatif. Tulisan ini berkontribusi pada model pengembangan akademik-keagamaan berbasis moderasi beragama di perguruan tinggi. Hal Membangun budaya akademik-keagamaan berbasis moderasi beragama penting untuk mencegah ekstremisme dengan memperkuat praktik keagamaan berdasarkan esensi ajaran agama.